ANGIOGENIC BLOOD CELLS AFTER LIVER TRANSPLANTATION - A. N. Shutko; O. A. Gerasimova; L. P. Ekimova; F. K. Zherebtsov (Вестник трансплантологии и искусственных органов)
Blood cells involved in neovascularisation were studied with flow-cytometry in the cadaver liver transplant recipients. The signs of «turbulent» state of bone marrow reproductive activity were found and assessed as features of its progressive exhaustion. The oscillations of regenerative capacity of angiogenic progenitor cells and angiogenic lymphocytes are discussed and considered to be the essential limiting factor influencing liver transplantation results. Further study of temporal variability of personal state of hematopoiesis is required for the improvement of posttransplant therapy.